DETECTION OF VIRULENCE GENES phoP AND phoQ IN Salmonella spp. USING IN SILICO POLYMERASE CHAIN REACTION - Stalis Norma Ethica; Hayatun Fuad; Nur Hidayah; Sri Sinto Dewi; Aditya Rahman Ernanto; Ayu Rahmawati Sulistyaningtyas; Richard David Silvestre; Sri Darmawati (Universitas Slamet Riyadi, 2020)
Detection of Salmonella bacteria based on their virulence genes is among essential steps in the eradication of clinical infection by bacteria. In this study, two pair of primers, PhoPF-PhoPR: 5’- CCGCGCAGGAAAAACTCAAA-3’ and 5’-ATCTGTTCCAGCATCACCGG -3’ as well as PhoQF-PhoQR: 5’-AGAGATGATGCGCGTACTGG-3’ and 5’- CAGACGCCCCATGAGAACAT-3’, had been successfully designed using Primer3Plus to detect the presence of phoP and phoQ genes in Salmonella spp. Using genomic DNA of 44 genomic data of Salmonella spp. as templates, PhoPF-PhoPR could produce 520-bp amplicon, while PhoQF-PhoQR could result in 598-bp amplicon. Results of in silico PCR showed that both pairs of primers PhoPF-PhoPR and PhoQF-PhoQR could detect only Salmonella enterica species, and no Salmonella bongori species could be detected based on phoP and phoQ sequences. Both pairs of PhoPF-PhoPR and PhoQF-PhoQR primers were also able to detect the virulence genes in most of the studied subspecies of Salmonella enterica available in silico database unless Arizona subspecies. As conclusion, based on this in silico study, phoP and phoQ genes appeared to be biomarkers for Salmonella enterica species. Both pairs of primers designed in this study has potential to be used as detection tool to differentiate species Salmonella enterica from Salmonella bongori, and also to distinguish S.enterica subsp. enterica from subsp. Arizonae.Keywords: Gene detection, bacterial virulence, phoP, phoQ, Salmonella spp.